Estimates of genetic parameters for visual scores and their correlation with production and reproductive traits in Brahman cattle - Bertipaglia, Tássia Souza [UNESP]; Carreño, Luis Orlando Duitama [UNESP]; Machado, Carlos Henrique Cavallini; Andrighetto, Cristiana [UNESP]; Fonseca, Ricardo da [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate the association of visual scores of body structure, precocity and muscularity with production (body weight at 18 months and average daily gain) and reproductive (scrotal circumference) traits in Brahman cattle in order to determine the possible use of these scores as selection criteria to improve carcass quality. Covariance components were estimated by the restricted maximum likelihood method using an animal model that included contemporary group as fixed effect. A total of 1,116 observations of body structure, precocity and muscularity were used. Heritability was 0.39, 043 and 0.40 for body structure, precocity and muscularity, respectively. The genetic correlations were 0.79 between body structure and precocity, 0.87 between body structure and muscularity, and 0.91 between precocity and muscularity. The genetic correlations between visual scores and body weight at 18 months were positive (0.77, 0.57 and 0.59 for body structure, precocity and muscularity, respectively). Similar genetic correlations were observed between average daily gain and visual scores (0.60, 0.57 and 0.48, respectively), whereas the genetic correlations between scrotal circumference and these scores were low (0.13, 0.02, and 0.13). The results indicate that visual scores can be used as selection criteria in Brahman breeding programs. Favorable correlated responses should be seen in average daily gain and body weight at 18 months. However, no correlated response is expected for scrotal circumference.
Keywords: average daily gain; body weight at 18 months; Genetic correlation; Heritability; scrotal circumference